2017
DOI: 10.5334/cstp.66
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Engagement Characteristics and Behaviours of Environmental Volunteers

Abstract: Environmental volunteering and environmental citizen science projects both have a pivotal role in civic participation. However, one of the common challenges is recruiting and retaining an adequate level of participant engagement to ensure the sustainability of these projects. Thus, understanding patterns of participation is fundamental to both types of projects. This study uses and builds on existing quantitative approaches used to characterise the nature of volunteer engagement in online citizen science proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 24 publications
(41 reference statements)
1
29
0
Order By: Relevance
“…The sample comprises of 952 volunteers each of whom completed a baseline survey, 161 completed a first follow up survey, and 63 completed a second follow up surveya response rate of 13.8% and 5.4% respectively. This attrition rate between surveys is consistent with participatory patterns of TCV volunteers identified by Seymour and Haklay (2016), where only a small proportion of volunteers continue to engage in long-term volunteering activities. Similar quantitative patterns are noted in other related volunteering studies (Reed and Selbee, 2001;Mohan and Bulloch, 2012;Hyde et al, 2016).…”
Section: Participating Programmessupporting
confidence: 79%
“…The sample comprises of 952 volunteers each of whom completed a baseline survey, 161 completed a first follow up survey, and 63 completed a second follow up surveya response rate of 13.8% and 5.4% respectively. This attrition rate between surveys is consistent with participatory patterns of TCV volunteers identified by Seymour and Haklay (2016), where only a small proportion of volunteers continue to engage in long-term volunteering activities. Similar quantitative patterns are noted in other related volunteering studies (Reed and Selbee, 2001;Mohan and Bulloch, 2012;Hyde et al, 2016).…”
Section: Participating Programmessupporting
confidence: 79%
“…Thus, we did not achieve our objective to have a high number of birdwatchers visiting the patch by themselves. We knew that engaging volunteers would be a difficult task (Chu et al 2012;Seymour and Haklay 2017;McKinley et al 2017;Frigerio et al 2018), but after our continuous efforts to recruit and interest birdwatchers proved successful, we were expecting more citizen scientists to participate in the field work.…”
Section: Project Applicants Versus Volunteers In the Fieldmentioning
confidence: 99%
“…A recent investigation of citizen science contribution tendencies across multiple projects has shown that a small number of participants, as few as 10%, make the majority of contributions to a project's total citizen science effort 15 . A similar investigation showed that an overwhelming majority of citizen science participants were classified as “One‐Time” or “One‐Session” volunteers 51 . Research on factors that motivate volunteers to continue participating in an extended citizen science program has identified interest in the topic, a strong sense of pride, wildlife encounters, and self‐interest in gaining research experience 16,49,52 .…”
Section: An Overview Of Citizen Sciencementioning
confidence: 99%
“…As mentioned above, volunteer retention can be a problem for citizen science practitioners 15,51 . To retain volunteers, scientists must understand that motivations change during the project, and this must be monitored and responded to 40 .…”
Section: Critical Challengesmentioning
confidence: 99%